High rates of elevated diabetes distress in research populations: A systematic review and meta-analysis. Issue 3 (2nd September 2015) - Dennick, Kathryn; Sturt, Jackie; Hessler, Danielle; Purssell, Edward; Hunter, Benjamin; Oliver, Jennifer; Fisher, Lawrence
Abstract : Diabetes distress has implications for diabetes end-points, hence targeted interventions are indicated; yet, preliminary work quantifying and characterising the problem is required. We sought to identify the potential magnitude and determinants of elevated diabetes distress across study populations. Databases such as Medline, PsycINFO and Embase were searched for studies ( n ≥50) administering the problem areas in Diabetes scale or Diabetes Distress scale, in adults with Type 1 or 2 diabetes. Random effects meta-analysis and meta-regression estimated the average rate of elevated diabetes distress and prognostic contribution of age, gender, HbA1c, and health-care context. Of the 16, 627 citations identified, adequate data were available for 58 studies. On average, 22% of participants reported elevated diabetes distress. Only female gender and secondary care predicted a higher rate of elevated diabetes distress. A quarter of people with diabetes have a level of distress likely to impact outcomes. Secondary-care practitioners should be vigilant of women with diabetes.